(untitled) (Eurasian Journal of Research, Development and Innovation, 2025)
This article discusses the issues of improving the methodology for developing the professional training of future engineers through digital technologies. The study identifies pedagogical, technological, and organizational-methodological conditions necessary for creating a digital educational environment in engineering education and proposes a step-by-step model for implementing the methodology. It is scientifically substantiated that the systematic integration of digital technologies into the educational process serves as a significant factor in enhancing the professional competencies of future engineers.